(untitled) (Research, Society and Development, 2022)
Objective: To present a case of neonatal uterine prolapse at a reference maternity hospital. Methodology: This is a case report of neonatal uterine prolapse that occurred at a tertiary maternity hospital in Manaus, Amazonas, Brazil. The data presented were collected from medical records that contained the history and reports of the examinations performed. Results and Discussion: The newborn was delivered vaginally in cephalic presentation. The apgar scores were 8 and 10 (at 1 and 5 min of life, respectively). On physical examination, the patient weighed 2,971 g, had mild edema, atypical facies, a visible increase in head circumference, flexed limbs, and reduced subcutaneous tissue. On the 4th postoperative day of myelomeningocele repair, a pinkish, edematous, interlabial mass was observed in the genital region, compatible with uterine cervix prolapse. At 15 days of age, a Foley probe No. 6 was inserted, inflated with 5 mL distilled water, and occluded with a dermal dressing concomitant with local estrogen application (1 mL) once a day. Conclusion: Uterine prolapse is a rare condition in newborns and is usually associated with spina bifida. The treatment is conservative in most cases, and the prognosis is generally favorable.